A língua de Sinais emergente como mediadora no processo socioeducacional de uma pessoa surda - PAIXÃO, José Aldeny Costa da (2025)
The discussion on bilingual education for the deaf has advanced a lot in recent decades. However, the schools still cannot offer a bilingual environment in which the Brazilian Sign Language (Libras) and the Portuguese Language as a second language (l2) can be the languages of instruction since the initial grades. The purpose of this article is to investigate the educational process of a deaf person who did not have Libras as her first language, based on the perspectives of bilingual education and the right to include deaf students in the regular system of education. For this, a case study was made and through observations data were collected with the complementation of interview with the participants. The results demonstrated that the deaf participant of this study had access to a bilingual environment, where the mediator language was an emerging sign language created by her that served as the basis for the acquisition of Libras and Portuguese l2 more effectively. Thus, we concluded that proposals for inclusion and bilingual education for the deaf still need a lot of reflection in order to actually meet the real needs of these students.